The Power of Imagination: Constructing Innovative Classrooms Through a Cultural-Historical Approach to Creative Education (LEARNing Landscapes, 2012)
All children have a need for and a right to educational programs that foster their creative ingenuity. This article presents a cultural-historical approach to creative education (CHACE) to cultivate K-5 students’ higher order thinking, critical inquiries, and imaginative proficiencies. The text illustrates the application of Vygotskian theory in elementary, bilingual classrooms where interdisciplinary, collaborative, and apprentice initiatives in the arts, humanities, and sciences facilitate the acquisition of literacy, numeracy, and content knowledge. Relationship, affect, and cognitive pluralism are discussed as theoretical cornerstones in a system of activities to nurture children’s novel interpretations, enhanced understandings, imaginative problem solving, critical innovations, and artistic creations within a supportive teaching-learning community
Keywords: cultural-historical approach to creative education (CHACE); K-5; critical inquiry; Vygotskian theory; elementary; bilingual; literacy; affect; cognitive pluralism; creativity